2014
DOI: 10.4193/rhin13.126
|View full text |Cite
|
Sign up to set email alerts
|

Nasal peak inspiratory flow (NPIF) as a diagnostic tool for differentiating decongestable from structural nasal obstruction

Abstract: NPIF increase after decongestion is larger with decongestable than structural nasal obstruction. NPIF alone cannot discriminate the two conditions and does not replace more formal assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
13
0
5
Order By: Relevance
“…The nasal decongestant eliminates the nasal cycle, 34 and is routinely used in assessment of the nose. 32 Our hypothesis is that specific nasal diseases display unique responses to decongestant and expands further on the decongestable and non-decongestable nasal obstruction hypothesis outlined by Chin et al 15…”
Section: Methods Of Studymentioning
confidence: 65%
See 1 more Smart Citation
“…The nasal decongestant eliminates the nasal cycle, 34 and is routinely used in assessment of the nose. 32 Our hypothesis is that specific nasal diseases display unique responses to decongestant and expands further on the decongestable and non-decongestable nasal obstruction hypothesis outlined by Chin et al 15…”
Section: Methods Of Studymentioning
confidence: 65%
“…14 However, NIPF cannot diagnose the cause of nasal blockage however changes in NIPF following decongestant can help in distinguishing the presence of decongestable nasal obstruction. 15 There is also an increasing drive from NHS England to streamline diagnostics in primary care and reduce secondary care referrals for ENT conditions which could be easily diagnosed and managed within primary care if the technology is available. 16 This would reduce the demand on costly secondary care services and improve cost efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst post-decongestant change in the measured values have been described as a way to distinguish between rhinitic and structural obstructions in the nose [29], we have shown that the post-decongestant effect could also be used to distinguish between different types of rhinitic conditions such as allergic rhinitis and CRS. The results in this study demonstrate a difference between the CRS group and the non-CRS groups, with the latter generally having higher postdecongestant percentage changes in both the NIPF and INA score (post-decongestant increase for the former, decrease for the latter).…”
Section: Discussionmentioning
confidence: 83%
“…This mucosal change of the inferior turbinate is irreversible and subsequently becomes non‐decongestable. Chin et al . defined these non‐decongestable patients as patients whose nasal peak inspiratory flow increases of less than 20 L/min after decongestion.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the eosinophil influx after nasal challenge with dust mites was reduced in the turbinoplasty group. Predecongestion and postdecongestion peak nasal inspiratory flows were suggested by Chin et al . for selecting patients suitable for inferior turbinate reduction.…”
Section: Discussionmentioning
confidence: 99%